An Investigation of the Metabolism and Excretion of KD101 and Its Interindividual Differences: A Microtracing Mass Balance Study in Humans. Issue 1 (26th September 2020) - Kim, Anhye; Dueker, Stephen R.; Hwang, Jun Gi; Yoon, Jangsoo; Lee, Sang‐Won; Lee, Hye Suk; Yu, Byung‐Yong; Yu, Kyung‐Sang; Lee, Howard
Abstract : The absorption, metabolism, and excretion (AME) profiles of KD101, currently under clinical development to treat obesity, were assessed in humans using accelerator mass spectrometry (AMS) after a single oral administration of KD101 at 400 mg and a microdose of 14 C‐KD101 at ~ 35.2 μg with a total radioactivity of 6.81 kBq. The mean total recovery of administered radioactivity was 85.2% with predominant excretion in the urine (78.0%). The radio‐chromatographic metabolite profiling showed that most of the total radioactivity in the plasma and the urine was ascribable to metabolites. The UDP‐glucuronosyltransferase (UGT), including UGT1A1, UGT1A3, and UGT2B7, might have contributed to the interindividual variability in the metabolism and excretion of KD101. The microtracing approach using AMS is a useful tool to evaluate the AME of a drug under development without risk for high radiation exposure to humans.